L’Algérie « post-décennie noire » : de l’imposition de l’impunité à la revendication d’une justice transitionnelle - Morgane Jouaret (L’Année du Maghreb)
This contribution proposes to look back at the process of “national reconciliation” after the black decade in Algeria (1992-1999) in order to analyze the co-construction of memorial narratives by institutional and associative actors. For the political authorities, the urgency of restoring peace was imposed in the face of the aspirations of a part of civil society, mainly the victims and their relatives, organized in associations and committed to a logic of truth and justice. This article proposes to analyze six “phases” of the national reconciliation policy in order to highlight the co-construction of the justice process, both by the State and by local victims’ associations. On the one hand, the national criminal justice system undertook to reduce violence by demobilizing combatants involved in armed Islamist groups (1995-1999) and to vertically pronounce “national reconciliation” (2006). On the other hand, local victims’ associations have internationalized their claims and mobilized the tools of transitional and restorative justice in order to bring out a “counter-narrative” of the war. This reflection is based on several ethnographic research fields conducted in Algiers and Oran between 2015 and 2019 as well as on the analysis of legal texts (the laws of 1995, 1999, 2006) and reports published on the internet by associations and NGOs (CFDA, SOS Disparus, Algeria Watch). The retrospective analysis of the hybridization of the “national reconciliation” process shows the confrontation of references to the past. The legal and judicial modalities that allowed the violence to stop have permanently compromised the construction of a national narrative to which.